2014
DOI: 10.1007/s12028-014-0013-9
|View full text |Cite
|
Sign up to set email alerts
|

Only Very Early Oxygen Therapy Attenuates Posthemorrhagic Edema Formation and Blood–Brain Barrier Disruption in Murine Intracerebral Hemorrhage

Abstract: Very early oxygen therapy can attenuate edema formation and BBB disruption after ICH, but the brief therapeutic time window suggests that the translational potential is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Hematoma volume is correlative to PHE (22). It is reported that the association between hematoma volume and PHE increases in large hematomas and decreases in small hematomas over time (44,48,51). Ambient temperature has association with PHE volume in acute spontaneous ICH (49).…”
Section: █ Discussionmentioning
confidence: 98%
“…Hematoma volume is correlative to PHE (22). It is reported that the association between hematoma volume and PHE increases in large hematomas and decreases in small hematomas over time (44,48,51). Ambient temperature has association with PHE volume in acute spontaneous ICH (49).…”
Section: █ Discussionmentioning
confidence: 98%
“…Plenty of studies suggest that HBO treatment is effective in brain injury at low altitude. Early HBO therapy mitigates blood–brain barrier disruption and suppresses the progression of brain edema post-ICH by preventing occludin degradation and matrix metalloproteinase-9 activation in the perihematomal tissue [ 36 ]. In a murine ischemic stroke study, altered striatal energy metabolites and glutamate can be regulated by HBO, which might contribute to the neuroprotection of HBO therapy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…(12) Hemorrhagic stroke which is more fatal and complex generally involves SAH and intracerebral hemorrhage (ICH) (Pandey and Xi, 2014). Effect of HBOT in hemorrhagic stroke was also studied in animals, mainly involving the suppression of brain edema, neuroinflammation, cerebral vasospasm and the promotion of both angiogenesis and neurogenesis (Peng et al, 2014;Xiong and Yang, 2015;Yang et al, 2015;Zhou et al, 2015). The associated molecular mechanism is basically consistent with that in ischemic stroke.…”
Section: Experimental Studies Of Hbot In Strokementioning
confidence: 91%